The Book Thief - Zusak, Markus; White, Trudy (New York : Alfred A. Knopf, 2013)
Trying to make sense of the horrors of World War II, Death relates the story of Liesel--a young German girl whose book-stealing and story-telling talents help sustain her family and the Jewish man they are hiding, as well as their neighbors.
Keywords: Books and reading -- Juvenile fiction; Storytelling -- Juvenile fiction; Death -- Juvenile fiction; Jews -- Juvenile fiction -- History -- 1933-1945 -- Germany; World War, 1939-1945 -- Juvenile fiction -- Jews; Books and reading -- Fiction; Storytelling -- Fiction; Death -- Fiction; Jews -- Fiction -- History -- 1933-1945 -- Germany; World War, 1939-1945 -- Fiction -- Jews; Germany -- Juvenile fiction -- History -- 1933-1945; Germany -- Fiction -- History -- 1933-1945